(untitled) (Third Sector Social Economic Review, 2025)
While the family court undertakes duties and responsibilities in protecting the interests of the parties and especially the children, securing their future, examining the psychological, social, economic and spiritual factors that will be created by the divorce process, it also provides solutions to types of cases such as adoption, establishment of personal relations and regulation of the right of custody. The support provided by social work academics in the psycho-social treatment of the aforementioned factors within the scope of family court constitutes a very important dimension. The main purpose of the research is; The aim of this study is to determine the opinions and evaluations of the academicians regarding the social review process that directly affects the cases in the family courts and how they perceive the process. In this study, in which the qualitative research method was used, the multiple case study design, which was handled under the interpretive paradigm, was used. In this context, data were collected by conducting in-depth interviews with 8 academics from social work backgrounds who work or have worked at universities. In the study, it has been evaluated that the effective and functional reflection of the social review process in the social review reports can only be possible if it is carried out by social workers, and it is also necessary to handle the reports in a structure that looks at interactions with the social environment, as well as containing an individual, family and child-oriented approach. In addition, it has been emphasized that social workers working in the field will improve their professional knowledge, values, observation and synthesis skills within the institutional structure and benefit from academic staff, which will positively affect the process.